Proceedings of the 9th Nordic Conference on Human-Computer Interaction 2016
DOI: 10.1145/2971485.2971509
|View full text |Cite
|
Sign up to set email alerts
|

Design Opportunities for Wearable Devices in Learning to Climb

Abstract: In this paper, we present a field study on the learning of climbing aimed at defining the design space of wearable devices to support beginners. Three main findings have emerged from our study. First, climbing has a strong emotional impact on beginners; therefore, learning to climb requires mastering new motor patterns as well as negative emotions, such as stress and fear. Second, the feeling of danger that climbers often experience can be mitigated by trust in the climbing partner and the perception of her ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
(18 reference statements)
0
13
0
Order By: Relevance
“…Two papers use a research-through-design approach [56], [60], while one employs design workshop activities [59]. One paper uses interviews with potential users [54], one adopts observation and semistructured interviews [55], and one employs content analysis of online reviews of wearable devices [57]. Others engage users through questionnaires or online surveys [53], [58], [61].…”
Section: A Research Perspectives and Methodological Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Two papers use a research-through-design approach [56], [60], while one employs design workshop activities [59]. One paper uses interviews with potential users [54], one adopts observation and semistructured interviews [55], and one employs content analysis of online reviews of wearable devices [57]. Others engage users through questionnaires or online surveys [53], [58], [61].…”
Section: A Research Perspectives and Methodological Approachesmentioning
confidence: 99%
“…Observation and contextual interviews, instead, are used to a much lesser extent. Mencarini et al [55] observed 6 indoor climbing lessons and interviewed 17 trainees and mountain guides, whereas Patel and O'Kane [74] observed 11 participants while exercising at the gym.…”
Section: A Research Perspectives and Methodological Approachesmentioning
confidence: 99%
“…Past work suggests that the number and complexity of available interactions under physical exertions (which cycling is likely to cause) should be limited. Wozniak et al [49] showed this requirement to be valid for running and Mencarini et al [29] for climbing. Their findings echo the constraints for interaction in motion as postulated by Marshall and Tennent [25].…”
Section: Input During Physical Activitymentioning
confidence: 99%
“…Taking tennis as a case study, it aims to recognize player shot types and measure ball states. Wearable devices have also been used in supporting the learning of climbing by providing the actors involved with augmented communication [9].…”
Section: Academic Researchmentioning
confidence: 99%